Os professores formadores do curso de licenciatura em matemática: condições da docência - Silva, Sandra Regina Lima dos Santos (2009)
This study aims to contribute to a reflection on the work of the trainer teacher who works in the courses of Degree in Mathematics. The study was initially justified by the importance of the work of those teachers who have direct involvement with the training of professionals who will work in elementary school, and also because of the small number of academic researches about this issue. When trying to understand the process of building these professional trainers, the study sought to answer the following questions: Who is the trainer teacher of the course of Degree in Mathematics? What are the challenges faced in their teaching as a trainer? What knowledge needed to face these challenges according to the trainer teachers? For this study was used the qualitative approach as a methodological procedure, and the main instruments for data collection used were interviews, observation and analysis of documents. The research subjects were four trainer teachers of a course of Degree in Mathematics from a private school of Greater São Paulo. The research has allowed to outline the profile of those teachers, to understand how they develop their work, to identify their professional knowledge and skills and the conditions under which the teaching is carried out. The theoretical assumptions, which anchored the study, relate to the professionalization of teachers, to the professional development and the knowledge mobilized by the trainers in the course of teaching. In general, the analysis of information obtained allows to say that this group of teachers has been devoted to the continuity of studies and sought a better qualification in order to act in the course of degree. It is a group that, given some features of work and condition, has demanded efforts in relation to the socialization of knowledge needed for teaching. The influences experienced by the old masters during the course of training and performance in basic education have proved of fundamental importance to their professional choices and actions. This research may show that the greatest challenge found in the path of the trainers is the work with the student. In confronting these challenges in their teaching, the trainer teachers mobilize different knowledge, which emerge as they develop their work